Teachers’ And Students’ Perspectives On The Impact Of English Clubs On Students’ Speaking Proficiency - Fazar Khoirul Iman; Rina Herlina; Wawan Tarwana (Universitas Galuh, 2026)
Students learning English as a Foreign Language (EFL) often struggle with speaking skills due to limited exposure to authentic communication and low confidence. These issues underscore the importance of examining how extracurricular activities, such as English clubs, can foster oral language development. This study examined the impact of English club participation on students’ speaking proficiency from the perspectives of both a teacher and students at a senior high school in Ciamis, Indonesia. A qualitative case study approach was employed, involving an interview with one English teacher and the completion of open-ended questionnaires by five English club members. Data were analysed using Braun and Clarke’s (2006) six-phase thematic analysis framework. Findings indicated that the English club was perceived as an effective platform for improving speaking ability. The teacher noted that the club provided meaningful speaking practice, enhanced student motivation, and reinforced classroom learning. Students described the club as enjoyable and supportive, with activities such as debates, storytelling, and role-plays that helped improve fluency and confidence. The findings showed that participation in the English club significantly increased speaking confidence, improved vocabulary use, and fostered more active communication among students. However, challenges such as limited vocabulary, time constraints, and initial nervousness were acknowledged by both the teacher and students. Despite these obstacles, students favoured the English club over traditional classroom methods. The study concludes that English clubs can positively influence speaking proficiency when designed with engaging, student-centred activities and supported institutionally. Future research is recommended to examine the long-term outcomes of participation and to explore the potential integration of digital tools or native speakers to enrich the learning experience further.